Evaluasi Reflektif Pengembangan Karakter Bangsa (Nasionalisme) Dalam Pendidikan Agama Buddha Tingkat Sekolah Dasar - Hesti Sadtyadi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
The Objective of this Study is to a reflective evaluation of Indonesian national character in the education of Buddhism in elementary schools, which can produce a picture that poures national values character (nationalism) in the context of learning that is administered. The reflective evaluation is carried out with the CIPP evaluation model, which includes five constructs and five reflective Buddhism educational instruments wich consits of context dimensions, the teacher’s interest, the teaching materials, the learning process and the product. All instruments are valid and reliable. The result of the development of the reflective evaluation instrument of Buddhist education that has been built consists of five aspects / dimensions of evaluation with the name Context, Teachers’ Knowledge / Interest (Input), Materials (Input), Process and Product (Product). The content of the nation’s character in Buddhism is explicit in the components of History, Faith (Saddha), Behavior or Morality (Sila), Buddhist holly Books (Tipitaka), Meditation (Samadhi), and Wisdom (Panna), accumulated in context, input, process, and output, through the evaluation of the Buddha’s education refelective in the development of the nation’s character.